2006
DOI: 10.1007/s10623-006-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

A random construction for permutation codes and the covering radius

Abstract: We analyse a probabilistic argument that gives a semi-random construction for a permutation code on n symbols with distance n − s and size (s!(log n) 1/2 ), and a bound on the covering radius for sets of permutations in terms of a certain frequency parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 13 publications
1
35
0
1
Order By: Relevance
“…Note that we are using a special and uncommon version of the lemma whose applications can be found in the proof on Latin transversals in [1], in [9], or in [2].…”
Section: Collection Of Events and For Anymentioning
confidence: 99%
See 2 more Smart Citations
“…Note that we are using a special and uncommon version of the lemma whose applications can be found in the proof on Latin transversals in [1], in [9], or in [2].…”
Section: Collection Of Events and For Anymentioning
confidence: 99%
“…Another dimension for further research stems from a certain semi-random construction that was considered by Ku-Keevash in [9]. In their paper, they utilized Theorem 3.4 to prove the existence of a randomized algorithm that, under certain conditions, constructs sets of permutations (from the underlying symmetric group S n ) that are <s-intersecting; that is, the sets constitute codes whose minimum distances are at least n − s + 1.…”
Section: Algorithmic and Asymptotic Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important result for PAs with minimum distances that are far away from both n and 0 appears in Keevash and Ku (2006). There, it is shown that a randomised algorithm can be used to produce a set of permutations subject to certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We refer the reader to [2,6] for related algebraic results, to [10] for a nice probabilistic approach, and to [3,15] for some combinatorial bounds.…”
mentioning
confidence: 99%